Heparan Sulfate Biosynthesis and Sulfation Profiles as Modulators of Cancer Signalling and Progression - Marques, Catarina; Reis, Celso A.; Vivès, Romain R.; Magalhães, Ana (Frontiers in Oncology, 2021)
Heparan Sulfate Proteoglycans (HSPGs) are important cell surface and Extracellular Matrix (ECM) maestros involved in the orchestration of multiple cellular events in physiology and pathology. These glycoconjugates bind to various bioactive proteins, via their Heparan Sulfate (HS) chains, and function as scaffolds for protein-protein interactions, modulating extracellular ligands gradient, cell signalling networks and cell-ECM interactions. The structural features of HS chains, including length and sulfation patterns, are crucial for the biological roles displayed by HSPGs, as these features determine HS chains binding affinities and selectivity. The large HS structural diversity results from a tightly controlled biosynthetic pathway that is differently regulated in different organs, stages of development and pathologies, including cancer. This review addresses the regulatory mechanisms underlying HS biosynthesis, with a particular focus on the catalytic activity of the enzymes responsible for HS glycan sequences and sulfation motifs, namely D-Glucuronyl C5-Epimerase, N- and O-Sulfotransferases. Moreover, we provide insights on the impact of different HS structural epitopes over HSPG-protein interactions and cell signalling, as well as on the effects of deregulated expression of HS modifying enzymes in the development and progression of cancer. Finally, we discuss the clinical potential of HS biosynthetic enzymes as novel targets for therapy, and highlight the importance of developing new HS-based tools for better patients’ stratification and cancer treatment.